2016
DOI: 10.1152/ajpheart.00114.2016
|View full text |Cite
|
Sign up to set email alerts
|

Defective branched chain amino acid catabolism contributes to cardiac dysfunction and remodeling following myocardial infarction

Abstract: Cardiac metabolic remodeling is a central event during heart failure (HF) development following myocardial infarction (MI). It is well known that myocardial glucose and fatty acid dysmetabolism contribute to post-MI cardiac dysfunction and remodeling. However, the role of amino acid metabolism in post-MI HF remains elusive. Branched chain amino acids (BCAAs) are an important group of essential amino acids and function as crucial nutrient signaling in mammalian animals. The present study aimed to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
161
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(171 citation statements)
references
References 22 publications
10
161
0
Order By: Relevance
“…Additionally, another BCAA metabolite released from skeletal muscle cells increases endothelial and skeletal muscle fatty acid uptake and can cause glucose intolerance (44), emphasizing the importance of BCAA metabolism in regulating metabolic health. Interestingly, myocardial BCAA metabolism is also altered in heart failure, a condition known to increase GRK2 signaling within the myocardium (45,46). It is possible that altered BCAA metabolism during HF due to enhanced GRK2 signaling could play an important role in modulating global health and insulin signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, another BCAA metabolite released from skeletal muscle cells increases endothelial and skeletal muscle fatty acid uptake and can cause glucose intolerance (44), emphasizing the importance of BCAA metabolism in regulating metabolic health. Interestingly, myocardial BCAA metabolism is also altered in heart failure, a condition known to increase GRK2 signaling within the myocardium (45,46). It is possible that altered BCAA metabolism during HF due to enhanced GRK2 signaling could play an important role in modulating global health and insulin signaling.…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that defects in BCAA catabolism could directly result in cardiac dysfunction and accelerate TAC-induced cardiomyopathy. Indeed, pharmacological inactivation of BCKDK by BT2 rescued the cardiac dysfunction, improved structural remodeling, and ameliorated post-MI heart failure progression (181), as well as preserving cardiac contractility and function in TAC-subjected mice (118), thus highlighting the potential of targeting BCAA catabolism as a therapeutic intervention for heart failure.…”
Section: Heart Diseasesmentioning
confidence: 98%
“…However, there is also evidence of their accumulation during HF, as seen in a study on failing mouse hearts where genes associated with amino acid catabolism were downregulated during compensated hypertrophy and overt failure ( 130 ). Transcriptomic analyses reflected downregulation of genes involved in amino acid degradation pathways [proline, alanine, tryptophan, and mainly branched-chain amino acids (BCAAs)] ( 131 133 ). Using a genetic mouse model, Sun et al demonstrated that a deficiency in BCAA catabolism induced heart failure under mechanical overload, resulting from increased oxidative stress ( 132 ).…”
Section: Cardiac Metabolismmentioning
confidence: 99%